Confirmed Mechanism for 1,8-Diaminonaphthalene and Ethyl Aroylpyrovate Derivatives Reaction, DFT/B3LYP, and Antimicrobial Activity of the Products - Sraa Abu-Melha (Journal of Chemistry)
Two new series of perimidine derivatives were prepared from the reaction of 1,8-diaminonaphthalene with ethyl aroylpyrovate followed by coupling for the products. The structures, the mechanism, and the tautomeric forms of the products have been discussed on the basis of spectral data aided with the computational study. Applying Guassian09 software, the reaction mechanism was assured. The energy contents were computed after optimization for all proposed structures. The likely extracted compound has a reduced heat during formation and internal energy which coincides with experimental outcomes. The antimicrobial activity of all products was screened, and their results indicated the presence of five derivatives more potent than the reference drugs used. The simulation procedure was executed by Autodock 4.2 tools over the expected compounds yielded (12 and 21). This computational technique asserts on the drug behavior inside the causative organism proteins. The organisms here match with that used in the antimicrobial and antifungal study.